PB DIFFUSION IN CR DIOPSIDE, AUGITE, AND ENSTATITE, AND CONSIDERATION OF THE DEPENDENCE OF CATION DIFFUSION IN PYROXENE ON OXYGEN FUGACITY - Cherniak D.J. (My University, 2001)
Chemical diffusion of Pb under anhydrous, pO2-buffered conditions has been measured in natural pyroxenes of three different compositions: a chromian diopside, an augitic clinopyroxene, and a near-end member enstatite. Sources of diffusant consisted of PbS powder and ground pyroxene mixed together, pre-reacted in evacuated silica capsules at 1050°C, and re-ground. Prepared sample capsules were annealed for times ranging from several hours to a few months, at temperatures from 850°C to 1050°C. The Pb distributions in the pyroxene specimens were profiled by Rutherford Backscattering Spectrometry (RBS).The following Arrhenius relations are obtained for Pb diffusion in the pyroxenes when buffered at QFM:DC=8.7x10-7exp(-351+/-36kJmol-1/RT)m2s-1.(Crdiopside)DA=3.8x10 -5exp(-372+/-15kJmol-1/RT)m2s-1.(augite)DE=6.6x10-7exp(-366+/-29kJm ol-1/RT)m2s-1.(enstatite)In all cases, diffusion is measured perpendicular to the c-axis. Diffusion in Cr diopside does not appear to be strongly anisotropic, as diffusion rates for transport parallel to c are similar to the (110) results above. Diffusion in the augite is faster (by nearly an order of magnitude) than Pb diffusion in the Cr diopside. Diffusion tends to be faster in pyroxenes with higher iron contents as was evident in our earlier work (Chemical Geology 150 (1998a) 105), but simple correlations are not obvious. Pb diffusion in enstatite is considerably slower than in the clinopyroxene compositions studied.To investigate the fO2 dependence of Pb diffusion in pyroxene, experiments using the Cr diopside, augite, and enstatite, as well as the near end-member diopside and a more iron rich clinopyroxene employed in a recent diffusion study (Chemical Geology 150 (1998a) 105), were run at 950°C under oxygen fugacities ranging from 10-6 to 10-16. All of the pyroxenes exhibited a positive dependence of Pb diffusion rate on fO2, with values of m ranging from 0.14 to 0.20, given D#(fO2)m. Interestingly, the exponential term for diopside is 0.19, in good agreement with the value +3/16 determined from point defect models for diffusion mechanisms controlled by cation vacancies (J. Geophys. Res. 99 (1994) 9423).The activation energies for Pb diffusion in all of the pyroxenes studied are relatively high, and Pb diffusivities slow when compared with the extant diffusion data for most other minerals. It follows, as consequence of these comparatively slow diffusivities, that Pb closure temperatures are higher in pyroxenes than for the majority of minerals, with the exception of a few phases such as zircon, monazite, and garnet. The slightly faster diffusivities that characterize Fe-rich clinopyroxenes will lead to somewhat depressed closure temperatures, but pyroxenes in general should be fairly retentive of Pb isotopic information when subjected to all but the most extreme thermal events.
Keywords: DIFFUSION; PYROXENE; OXYGEN FUGACITY; LEAD; RUTHERFORD BACKSCATTERING